Assessing the potential return on investment of the proposed UK NHS diabetes prevention programme in different population subgroups: an economic evaluation. Issue 8 (21st August 2017) - Thomas, Chloe; Sadler, Susi; Breeze, Penny; Squires, Hazel; Gillett, Michael; Brennan, Alan
Abstract : Objectives: To evaluate potential return on investment of the National Health Service Diabetes Prevention Programme (NHS DPP) in England and estimate which population subgroups are likely to benefit most in terms of cost-effectiveness, cost-savings and health benefits. Design: Economic analysis using the School for Public Health Research Diabetes Prevention Model. Setting: England 2015–2016. Population: Adults aged ≥16 with high risk of type 2 diabetes (HbA1c 6%–6.4%). Population subgroups defined by age, sex, ethnicity, socioeconomic deprivation, baseline body mass index, baseline HbA1c and working status. Interventions: The proposed NHS DPP: an intensive lifestyle intervention focusing on dietary advice, physical activity and weight loss. Comparator: no diabetes prevention intervention. Main outcome measures: Incremental costs, savings and return on investment, quality-adjusted life-years (QALYs), diabetes cases, cardiovascular cases and net monetary benefit from an NHS perspective. Results: Intervention costs will be recouped through NHS savings within 12 years, with net NHS saving of £1.28 over 20 years for each £1 invested. Per 100 000 DPP interventions given, 3552 QALYs are gained. The DPP is most cost-effective and cost-saving in obese individuals, those with baseline HbA1c 6.2%–6.4% and those aged 40–74. QALY gains are lower in minority ethnic and low socioeconomic status subgroups. Probabilistic sensitivity analysis suggests that there is 97% probability that the DPP will be cost-effective within 20 years. NHS savings are highly sensitive to intervention cost, effectiveness and duration of effect. Conclusions: The DPP is likely to be cost-effective and cost-saving under current assumptions. Prioritising obese individuals could create the most value for money and obtain the greatest health benefits per individual targeted. Low socioeconomic status or ethnic minority groups may gain fewer QALYs per intervention, so targeting strategies should ensure the DPP does not contribute to widening health inequalities. Further evidence is needed around the differential responsiveness of population subgroups to the DPP.